Energy and Economic Costs of Chemical Storage - Dias, Véronique; Pochet, Maxime; Contino, Francesco; Jeanmart, Hervé (Frontiers in Mechanical Engineering, 2020)
The necessity of neutralizing the increase of the temperature of the atmosphere by the reduction of greenhouse gas emissions, in particular carbon dioxide (CO2), as well as replacing fossil fuels, leads to a necessary energy transition that is already happening. This energy transition requires the deployment of renewable energies that will replace gradually the fossil fuels. As the renewable energy share increases, energy storage will become key to avoid curtailment or polluting back-up systems. This paper considers a chemical storage process based on the use of electricity to produce hydrogen by electrolysis of water. The obtained hydrogen (H2) can then be stored directly or further converted into methane (CH4 from methanation, if CO2 is available, e.g. from a carbon capture facility), methanol (CH3OH, again if CO2 is available), and/or ammonia (NH3 by an electrochemical process). These different fuels can be stored in liquid or gaseous forms, and therefore with different energy densities depending on their physical and chemical nature. This work aims at evaluating the energy and the economic costs of the production, storage and transport of these different fuels derived from renewable electricity sources. This applied study on chemical storage underlines the advantages and disadvantages of each fuel in the frame of the energy transition.